Treatment of maxillary transverse deficiency with rapid expansion of the palate with mini-implant: a review - Duque-Urióstegui, Cristhal; Ramírez Reyes, Yocelin; González Rodríguez, Magali; López Portillo, Fernando; Castañeda Palacios, Gabriela; Briseño Flores, Carlos; Flores Estrada, Rosa; Flores Estrada, María del Rocío; Pliego, Ana Lilia Abundez; Barrera-Mera, Baltazar (International Journal of Research in Medical Sciences, 2023)
One of the most prevalent malocclusions is maxillary constriction, which is a narrowing of the upper arch; its etiology is multifactorial, including mainly genetic factors and parafunctional habits. It is characterized by a posterior crossbite that can be unilateral or bilateral, total or partial, and may even not occur in cases with simultaneous constriction of the mandibular arch. Transverse deficiency or maxillary hypoplasia affects facial growth and the integrity of the dentoalveolar structures. Therefore, it must be corrected as soon as it is diagnosed. As the maxilla widens, the midpalatal suture and the intermaxillary suture expand. When they are not fused, it is connective tissue and behaves viscoelastically in response to externally applied forces. In order to effectively treat any dentofacial deformation, an early diagnostic and therapeutic approach is required.